Raman spectroscopic study of hydrous wadsleyite (beta-Mg2SiO4) to 50 GPa - Kleppe, A; Jephcoat, A; Olijnyk, H; Slesinger, A; Kohn, S; Wood, B (2001)
Raman spectra of hydrous β-Mg2SiO4 (1.65 wt% H2O) have been measured in a diamond-anvil cell with helium as a pressure-transmitting medium at room temperature to 50 GPa. We observe three OH-stretching modes, a doublet with components at 3329 and 3373 cm-1, which decrease linearly with pressure, and a single mode at 3586 cm-1, which remains nearly constant up to 24 GPa before decreasing at higher pressures. Assessment of the mode frequencies and their pressure dependence, together with previous results from X-ray and IR data, are consistent with protonation of the O1 site in agreement with previous studies. Strict assignment of Raman activity awaits detailed structural models. The nature of the protonation in wadsleyite may require more specific experimental probes for full solution of the hydrogen-site problem.